BIM Policy in Eastern Europe - Mitera-Kiełbasa, Ewelina; Zima, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The European Union in the Industry 5,0 proposal encourages technological transformation. ICT Information and Communications Technology, which for the AEC industry are BIM and Digital Twin is appreciated, but also innovative and variable over time. Therefore publications like this, which verify the validity of information are important. Global BIM policy analysis can be valuable for stakeholders of the investment process, policymakers, researchers.
Keywords: BIM policy; BIM mandatory; BIM mandate; BIM implementation; ICT; AEC; industry 5.0